The relationship between organisational leadership and job satisfaction of three generational age groups in a school context - Haasbroek, Juan Gert Diedericks (Rhodes University, Faculty of Commerce, Rhodes Business School, 2021)
With multiple generations in education, there are different leadership styles preferred by schoolteachers that affect their job satisfaction (Cufaude and Riemersma, 1999:1-3). Schools should ensure that leadership works toward satisfied teachers to reach sustainable organisational performance. The resource-based view argues that organisations should look within the organisation, particularly human resources, to find sources that lead to improved organisational performance (Jurevicius, 2013:1). Therefore, organisations should equip themselves with the required leadership style(s) to meet employee expectations. Furthermore, it is imperative to look at different generations within the school's context, as it will strengthen or weaken the relationship between organisational leadership and job satisfaction. The study adopted a quantitative approach, using the Multiple Leadership Questionnaire and the Minnesota Satisfaction Questionnaire as instruments for collecting primary data. The population consists of high school teachers in the Eden District, Western Cape that work at affluent schools, which are declared as quantile 4 and 5 model schools. There is a total of 13 high schools that fall within this specification with a total population of 220 teachers. In total, 111 questionnaires were distributed, of which 73 were returned. Sixty-eight were considered usable. Both sample parameters specified by the research instruments were met. The primary purpose of the study was to investigate the relationship between leadership within the organisation (referring to transformational, transactional, and passive-avoidant organisational leadership styles) and employee job satisfaction of high school teachers in the Eden District. Different generations, from the age group perspective, is composed as a moderating variable in the relationship between organisational leadership and job satisfaction. The empirical study established that the independent variables, the leadership styles employed by the organisation, are directly related to employee job satisfaction. Of the three independent variables, transformational leadership and, to a lesser extent, transactional leadership proved to have a positive association with job satisfaction. In contrast, passive-avoidant leadership has a negative relationship with job satisfaction. It is also established that the relationship is stronger or weaker based on generations, positioning generations from the age group perspective as satisfactory moderator. It was found that Millennials prefer the transactional leadership style as this will strengthen the relationship between organisational leadership and job satisfaction. Baby Boomers prefer transformational leadership for the greatest positivity. To a lesser extent, transactional leadership will also contribute to the relationship's strength between organisational leadership and job satisfaction. Generation X is indifferent to transactional or transformational leadership.
Keywords: Educational leadership -- South Africa; High Schools -- Administration -- South Africa -- Western Cape; Management; High school teachers -- South Africa -- Western Cape -- Case studies; High school teachers -- South Africa -- Western Cape -- Job satisfaction; High school teachers -- South Africa -- Western Cape -- Attitudes